Oral rehydration salts, zinc supplement and rota virus vaccine in the management of childhood acute diarrhea - Abdulwahab MA Telmesani (Wolters Kluwer Medknow Publications, 2010)
Acute diarrhea remains a major cause of morbidity and mortality in children. Since the introduction of oral rehydration salts (ORS) mortality has dropped to less than 50% worldwide. Low osmolarity ORS improved the outcome and reduced the hospitalization further. Zinc difficiency has been found to be associated with severe episodes of acute diarrhea. Zinc supplement in developing countries did reduce the incidence and prevalence of diarrhea. In addition, Zinc supplement significantly reduced the severity of diarrhea and duration of the episode. In the Americas and Europe, Rota virus vaccine was 90% effective in preventing severe episodes of severe rotavirus gastroenteritis. This review concludes that low osmolarilty ORS, zinc supplementation and rotavirus vaccine are major factors in reducing the morbidity, mortality and hospitalization resulting from to acute gastroenteritis in childhood.